Method for organic fluorine determination in gasoline and its components using high-resolution continuum source flame molecular absorption spectrometry with gallium fluoride as a target molecule - Zofia Kowalewska (Elsevier, 2021)
Organic fluorides can arise due to the usage of HF in technologies of gasoline production, therefore, it is necessary to identify contamination of gasoline or its components with organic fluorine. For this aim, simple and fast method is proposed. The method relies on sample dilution in xylene, followed by the solution aspiration to a high-resolution continuous source spectrometer for measurement of absorption of radiation by GaF molecule, arisen in air-acetylene flame. Gallium(III) acetylacetonate is carefully dissolved and introduced to all measured solutions at Ga concentration 5000 mg L−1. For standard addition calibration three types of samples solutions are prepared to contain: none, 50 mg L−1 and 100 mg L−1 of added fluorine. As fluorine standard 2, 2, 3, 3, 4, 4, 4-heptafluoro-1-pentanol is applied. The lowest possible flow rate of acetylene is recommended. The solution flow rate and the additional air flow rate should be adjusted to obtain not-disturbed baseline. The overlap of the GaF signal with residual signal of the OH molecule can be overcome using least square background correction. Five pixels are recommended for signal evaluation at the most sensitive 211.248 nm rotational “line”. Using such conditions characteristic concentration was 3.2 mg L−1. Detection limit recalculated for initial sample was 4-10 mg L−1. • High-resolution continuum source flame molecular absorption spectrometry turned out to be an excellent tool for determination of pollution of gasoline with organic fluorine. • Due to application of GaF as a target molecule, it is possible to use a low-temperature and easy for operation air-acetylene flame. • The proposed method can be applied for analysis of alkylate, reformate, isomerizate, ethanol as well as commercial automotive and aviation gasoline.